Embedded conceptual understanding: a Kantian answer to the Dreyfus- McDowell debate (2023)
In recent years Hubert Dreyfus and John McDowell have debated in several of their works around the pervasiveness of conceptuality in human experience. Dreyfus offers a theory of experience whereby conceptual activity is seen as derivative to what he regards as the more basic phenomenon of our skillful, embodied engagement with the world (what he calls "skillful coping"). McDowell responds alternatively by defending the conceptual nature of skillful coping, claiming with the help of some original Kantian interpretation, that the conceptual is "unbounded". We argue that while McDowell is correct concerning the pervasively conceptual nature of experience, Dreyfus is right to insist on the importance of our skillful and unreflective bodily practices. Dreyfus, however, misunderstands the relationship between coping and conceptuality, and therefore, is unable to work out how we go from unreflective action to a reflective, self- critical stance towards the world. This leaves him with a problematic dualism in his vision of human being. McDowell, on the other hand, lacks the phenomenological tools to explain his claim that conceptual capacities are always operational even in unreflective activity. We argue that explaining this premise will pave the way forward towards a broader understanding of conceptuality, and thereby, a resolution of the dispute. Specifically, our claim is that a reconstruction of the Kantian idea of the role of imagination in synthetizing sensory experience -through the lens of the reading inauguratedby Wilfrid Sellars and followed to an extent by John McDowell himself-, will set the stage for a more careful analysis of reflective and unreflective experience. In this sense, we argue that possessing conceptual capacities -no less than having skillfully engaged bodies- shapes the content and nature of human perception. Ultimately, parting from an analysis of some fundamental Kantian doctrines such as his Deduction and Schematism, we argue for a non- propositional notion of conceptuality that allows us to set forth an account of the way our conceptual capacities suffuse sensory experience "from the ground up".